Video Online Learning: An Alternative for Students' Mathematics Problem Solving - Lestari, Fitria; Efendi, Deni; Dara, Triyana (Bulletin of Science Education, 2023)
The research design used quantitative in control group design (pretest-posttest control group design). The population in this study were all students of class VIII at SMP Muhamamdiyah 3 Bandar Lampung, totaling 147 students. The sampling technique used purposive sampling technique with the consideration that the selected sample was taught by the same teacher. For this reason, there were 2 sample classes, namely the experimental class, which consisted of 29 students and the control class, which consisted of 29 students. Data collection techniques were obtained through problem solving ability tests, observation. Based on the results of the analysis, it was obtained that there is a significant influence between classes using problem solving assisted learning online learning videos and classes using conventional learning models testing criteria with a significance level of 0.05. It was found that the results of the Sig t-test, (2 tailed) in both sample classes is 0.000 <0.05, then Ho is accepted meaning: there is a significant difference in effect between classes using problem solving learning assisted by online learning videos and classes using conventional learning models. Keywords: Problem Solving, Online Learning Videos, Mathematical Problem Solving Skills